2008
DOI: 10.1002/rra.1091
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of water quality in some rivers with different degrees of development within the São Paulo State, Brazil

Abstract: Time series of dissolved oxygen (DO), biochemical oxygen demand (BOD), nitrate, total phosphorus, chloride, ammonia and faecal coliforms (FC), monitored by CETESB ('Companhia de Tecnologia de Saneamento Ambiental'), in the period from 1979 to 2001, were analysed in seven river basins located in the São Paulo State, one of the most developed regions in Brazil. The selected rivers, Piracicaba, Mogi-Guaçu, Turvo Grande, Peixe, Aguapeí, São José dos Dourados and Alto Paranapanema have different degrees of developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 32 publications
1
25
0
10
Order By: Relevance
“…For instance, according to Dedini S/A [32], a company devoted to building sugar and ethanol industrial plants, technology that allow mills to generate water extracted from sugarcane is already available and can potentially decrease the consumptive use of water by sugarcane mills to almost zero. This gain in water use efficiency is especially important because most of the water is withdrawn by the sugarcane industry from 1st order streams and small rivers (Figure 1), which are already under intensive pressure due to the heavy loads of untreated domestic sewage [33][34][35], and increasing non-point sources of pollution from agricultural [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, according to Dedini S/A [32], a company devoted to building sugar and ethanol industrial plants, technology that allow mills to generate water extracted from sugarcane is already available and can potentially decrease the consumptive use of water by sugarcane mills to almost zero. This gain in water use efficiency is especially important because most of the water is withdrawn by the sugarcane industry from 1st order streams and small rivers (Figure 1), which are already under intensive pressure due to the heavy loads of untreated domestic sewage [33][34][35], and increasing non-point sources of pollution from agricultural [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Further, many studies have found untreated sewage to be the most critical issue with respect to water contamination, because 40% of the global population do not have adequate sanitary facilities [5,6]. Changes to land use, land cover or river basins in watershed areas, such as high scale agricultural activities, unplanned infrastructure developments, and sand mining, change the water quality and water balance due to human activities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the contents of untreated disposal or spatial disposal items such as organic materials, salinization, nutrients, suspended sediment, enteric virus, and oil and grease are directly affecting the water quality in river basins [7,8]. Furthermore, the aquatic chemical composition is possibly influenced by human activities [6]. This may be caused by improperly planned urbanization or uncontrolled development [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that population growth and industrial activities are drivers of water quality change. Groppo et al [10] found that population growth and increases in untreated sewage were the main causes of water quality deterioration in rivers in the State of Sao Paulo, Brazil. Ma et al [11] found that sharp increases in industrial pollution and domestic discharge were the major causes of water quality deterioration in the Shiyang River, Northwest China.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers found that such deterioration is due to the complex interaction between engineered infrastructures and social, economic, legal, and political issues during rapid urbanization [16,17]. However, most research addressed water quality change in urbanized areas rather than catchments in the process of rapid urbanization [6,10]. Furthermore, even fewer studies have investigated the integrated impact of socio-economic and infrastructure development on changes in water quality [16].…”
Section: Introductionmentioning
confidence: 99%